Localizing climate action in cities: Applying historical ecology to urban climate governance - Christopher C. Graham (Global Environmental Change Advances)
Cities are at the epicenter of global climate action. As a feature of urban climate governance, several major cities across the United States have developed multi-year action plans to conceptualize and coordinate their climate mitigation and adaptation efforts. For certain cities, these plans have been transformative. Leveraging resources and policy processes, they integrate climate resilience-building into long-term planning and urban development projects. However, the literature and practice of urban climate governance typically exist between the present and the future. There is relatively minimal regard for the historical forces that have shaped regional ecologies and cities, some for hundreds of years. Drawing upon historical ecology approaches, utilizing geoinformatics, and conducting quantitative and qualitative content analysis of city-specific climate action plans, this study examines how and why cities are applying historical knowledge and ecological principles in urban climate governance. The findings indicate that city planners and officials are increasingly integrating ecological practices and historical knowledge systems as a means of localizing, customizing, and better contextualizing climate action, particularly focusing on reducing combined risks in highly susceptible communities and urban landscapes. Green engineering and infrastructure, water resource management, and urban biodiversity enhancement are areas where this application has been most evident. Cities nevertheless encounter significant governance challenges in meeting the desired climate action outcomes. The results suggest that limited availability of historical data, ethical considerations regarding the use of Indigenous knowledge, climate solutions disparities, and historical path dependency are among the main limiting factors.